PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ADOBE FLASH CS6 PADA MATA PELAJARAN IPS KELAS VIII SMP - Andra Alwanda Putri; Zuwirna Zuwirna (Journal of Pedagogy and Online Learning, 2022)
The development of interactive multimedia based on Adobe Flash CS6 is one of the efforts to assist teachers in teaching and assisting students in understanding the material presented, can increase students' motivation, interest and memory in understanding learning. This interactive multimedia development research aims to produce interactive learning media products in social studies subjects as tools or media that are in accordance with the media and material eligibility criteria. This research is a development research known as Research and Development (R&D). The research procedure used in this development uses 4D stages consisting of the definition stage (Defind), the planning stage (Design), the development stage (Development), and the dissemination stage (Disseminate). Data collection techniques in this study used validation sheets and student response questionnaires. The product validity test was carried out by three validators consisting of two media experts and one material expert. The practicality test subjects were taken as many as 25 students of class VIII SMPN 3X11 Kayutanam for the 2022/2023 academic year. by 97.69%. and the results of validator II obtained an average of 99.23%. So that the overall results obtained an average of 98.46% in the "Very Eligible" category. While the results of the material expert validation are also categorized as "Very Appropriate" for use with a value of 93.33%. Furthermore, the results of the practicality test of interactive multimedia products are in the "Very Appropriate" category for use with an overall average of 90.47%. one learning media and can help the learning process more interesting and can increase student enthusiasm in the learning process.